Produção e certificação de materiais de referência biológicos para uso veterinário: Estirpes de Clostridium botulinum tipos C e D, suas toxinas e antitoxinas - Roseane Brandão de Brito (2019)
Botulism is a serious disease that affects humans and animals, caused by the action of botulinum neurotoxins (BoNT) produced by Clostridium botulinum. Types C, D and mosaics C /D and D/C are the main cause of disease in animals. Botulism in ruminants in Brazil changed from an endemic disease in the 1980s to 1990s, to sporadic outbreaks in recent years, mainly due to the successful implementation of the national control program based on systematic herd vaccination, as well as practices management. Botulinum toxins and botulinum toxins types C and D are essential inputs used in production, quality control and official testing of botulism vaccines. These inputs also have an important use in diagnosis of suspected cases of botulism, and in validation of new diagnostic methods, especially alternative methods to mouse bioassay. Equally important and necessary is the characterization of Clostridium botulinum strains, which can currently be performed by molecular and genomic techniques, in order to typify them considering the mosaic types, without any misunderstandings arising from cross reactions, which may occur in bioassay. The demand for more accurate and reliable data in scientific and technological areas has demanded higher quality reference materials. However, a major bottleneck is the dependence on imports of these materials, or even unavailability in the market. There are also added restrictions on bioterrorism, which prevent import of botulinum toxins or toxigenic strains. The objectives of this work were to characterize and certify batches of Clostridium botulinum strains, toxins and botulinum toxin types C and D, as certified reference materials (CRMs). With the use of classical microbiological methods, molecular techniques and genomic sequencing, it was possible to typify and characterize samples of Clostridium botulinum types C, D and D / C currently maintained by the official agency (MAPA) and veterinary industries, including genomic comparisons with other sequences available on GenBank. Batches of Clostridium botulinum strains type C (CBC 02) and type D (CBD 09), sufficiently homogeneous and stable were produced and certified as CRMs. Botulinum toxins and botulinum antitoxins types C and D produced in this work were considered homogeneous and stable after statistical tests based on regression analysis, except botulinum toxin type C (Batch 01/2016), which presented instability. The characterization was performed through a collaborative study between seven Brazilian institutions, including vaccine manufacturers and diagnostic laboratories. Reference values were estimated by measuring model with statistical independence, obtaining materials with the following titers and uncertainties: Botulinum toxin type C (Batch 01/2017), 55 ± 13 IU; Botulinum toxin type D (Batch 01/2017), 950 ± 153 L+; Botulinum antitoxin type D (Batch 01/2017), 50 ± 13 IU. Recommended temperature for storage of the products was ≤ -20ºC, and periods of validity of 10 years for strains and of one year for toxins and antitoxins, which could be extended, after complementary studies of monitoring the CRMs. The domain of production methodologies and certification protocols, meeting the requirements of internationally recognized quality standards for production of CRMs, provided availability of high quality products, indicated for use in tests for bacterial identification, quality control of vaccines against botulism, validation of methods, establishment of traceability to other materials, monitoring of laboratories and proficiency tests. In addition, it brought scientific advantage and independence to the country, adding reliability to the botulism control, and minimizing customs difficulties and costs involved in obtaining these inputs.